Fostering Emotional Discipline Through Intensive Qur’anic Repetition (Muraja’ah) in Islamic Boarding Schools - Izzatul Munawwaroh; Zohaib Hassan Sain (Indonesian Journal of Islamic Religious Education, 2026)
This study examines the contribution of intensive muraja'ah (recitation) in the takhassus program to strengthening the retention of Quranic memorization and emotional regulation of students. Using a qualitative approach through participant observation, in-depth interviews, and documentation, this study reveals how the practice of repeating Quranic verses plays a role in developing emotional discipline. The results show that intensive muraja'ah not only improves the accuracy and fluency of memorization but also trains focus, patience, and self-control, which support students' emotional stability. Collective muraja'ah activities also foster emotional solidarity through togetherness, empathy, and mutual support among participants, creating a harmonious and supportive learning environment. Thus, intensive muraja'ah has a dual effect: strengthening individual cognitive and emotional capacities while simultaneously developing social cohesion. This study contributes to the development of religious education by confirming that intensive Quranic repetition can be an effective pedagogical strategy for fostering emotional and spiritual maturity. The practical implications emphasize the importance of synergy between individual practice and collective activities in the takhassus curriculum so that students can achieve a balance between mastery of memorization, inner peace, and social engagement